Comprehensive insights into the structural, mechanical, electronic and thermodynamic properties of ε-Fe3Cr4C3 - Zixuan Xie; Tingping Hou; Junwen Duan; Xuan Liang; Yihang Zheng; Tao Yu; Gengping Jiang; Tianliang Zhao (Materials Research Express)
The mechanical, electronic and thermodynamic properties of alloy carbide ε -Fe _3 Cr _4 C _3 under varying temperature and pressure were systematically investigated using first-principles calculations and the quasi-harmonic Debye model. ε -Fe _3 Cr _4 C _3 maintains thermodynamic and mechanical stability across the investigated pressure range. Increasing pressure enhances its thermodynamic stability and reduces elastic anisotropy. The electron density distribution indicates stronger metallic bonds under high pressure, providing an explanation for the increased Young’s modulus. Concurrently, the rise in Debye temperature implies enhanced interatomic bonding forces, correlating with improved toughness and hardness. Ultimately, the sample of ε -Fe _3 Cr _4 C _3 was prepared through mechanical alloying and sintering. The experimentally measured hardness is in basic agreement with the theoretical predictions. This work lays essential theoretical foundations for understanding and predicting the properties of ε -Fe _3 Cr _4 C _3 in high pressure and high temperature applications.